Upaya Meningkatkan Manajemen Sumber Daya Manusia, Gaya kepemimpinan, Komitmen organisasi dan Peningkatkan Kinerja Karyawan dalam Penanganan konflik Industri Di Dinas Tenaga Kerja, Transmigrasi dan Energi Prov. DKI jakarta - Nining, Andria Ningsih; Dasep Suryanto; Zuripal, Zuripal; Dona Amelia (Jurnal Pengabdian Kepada Masyarakat, 2023)
This PKM is carried out at the Manpower, Transmigration and Energy Department of DKI Jakarta Province. Jl. H. Naman No.1 RT.1/RW.3, Pd. Klp., District. Duren Sawit, East Jakarta City, Special Capital Region of Jakarta. Currently, employees of the Department of Manpower, Transmigration and Energy are facing various cases of implementing conflicts in the industry that have come but have not been able to overcome them all because the leadership style, organizational commitment and employee performance have not been implemented correctly. Human resource management is a process of dealing with various problems within the scope of employees, employees, workers, managers and other workers to be able to support the activities of an organization or company in order to achieve predetermined goals. To overcome a number of problems faced by this group, solutions with optimal HR management strategies are needed. The methods used in providing community service counseling and training are pretest, lecture, media outreach, and posttest. Based on the results and discussion, it can be concluded that this service activity provided positive results. Because this activity can help employees of the Manpower, Transmigration and Energy Department understand the need for HR management and leadership style, organizational commitment, employee performance in helping with implementation cases in overcoming conflicts in industry so that they have the quality and quality of being a mentor. So that you can implement and solve all the problems that exist in the industry.